2002
DOI: 10.1079/bjnbjn2001517
|View full text |Cite
|
Sign up to set email alerts
|

Procyanidins are not bioavailable in rats fed a single meal containing a grapeseed extract or the procyanidin dimer B<SUB>3</SUB>

Abstract: Flavanols are the most abundant flavonoids in the human diet where they exist as monomers, oligomers and polymers. In the present study, catechin, the procyanidin dimer B 3 and a grapeseed extract containing catechin, epicatechin and a mixture of procyanidins were fed to rats in a single meal. After the meals, catechin and epicatechin were present in conjugated forms in both plasma and urine. In contrast, no procyanidins or conjugates were detected in the plasma or urine of any rats. Procyanidins were not clea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…In the present study, proanthocyanidins up to nonamers and substantial but undetermined high molecular weight polymeric proanthocyanidins were detected. One of the major questions has been whether the high molecular weight proanthocyanidins are bioavailable in detectable amounts (Donovan et al, 2002). It has been suggested that the effects of dietary proanthocyanidins are unlikely to be due to proanthocyanidins themselves or monomeric metabolites with the intact flavonoid-ring structure, as they do not exist at detectable concentrations in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, proanthocyanidins up to nonamers and substantial but undetermined high molecular weight polymeric proanthocyanidins were detected. One of the major questions has been whether the high molecular weight proanthocyanidins are bioavailable in detectable amounts (Donovan et al, 2002). It has been suggested that the effects of dietary proanthocyanidins are unlikely to be due to proanthocyanidins themselves or monomeric metabolites with the intact flavonoid-ring structure, as they do not exist at detectable concentrations in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Spencer and co-workers (Spencer, Chaudry, Pannala et al, 2000) have demonstrated that proanthocyanidins undergo partial acid-catalyzed cleavage into their monomeric flavan-3-ol units in the gastric milieu. However, others have disputed the contribution of gastric depolymerization to the bioavailability of the constituent catechin units of proanthocyanidins (Donovan, Manach, Rios et al, 2002). …”
Section: Carbon-carbon Cleavage Reactionsmentioning
confidence: 99%
“…Their monomeric units [(+)-catechin and (-)-epicatechin)] are linked through a C4-C8 or C4-C6 bond (B-Type), which can coexist with an additional C2-O-C7 bond (A-Type). Absorption of procyanidins after food intake has been reported in several earlier studies (Donovan et al, 2002;Groenewoud & Hundt, 1986;Van'T Slot, Mattern, Rzeppa, Grewe & Humpf, 2010) and it is known that only procyanidin dimers are believed to be absorbed intact, although with lower efficiency than the monomeric units (Appeldoorn, Vincken, Aura, Hollman & Gruppen, 2009). Due to the low absorption of intact procyanidins, gut microbial metabolism might play an important role.…”
Section: Introductionmentioning
confidence: 88%
“…Oligomers and polymers are called proanthocyanidins or condensed tannins, and they are some of the most abundant phenolic compounds in some foods such as cacao, tea and wine (Gu et al, 2004). They are mainly made up of (epi)catechin or (epi)gallocatechin units that are known as procyanidins or prodelphinidins, respectively (Donovan, Manach, Rios, Morand, Scalbert & Rémésy, 2002).…”
Section: Introductionmentioning
confidence: 99%